RETRACTED PAPER: Circ_0067835 acts as an oncogenic factor in colorectal cancer by increasing MAPK1 expression via sponging miR-873-5p - Shouchao Li; Feifei Sun (Journal of Biological Research - Thessaloniki, 2022)
Many circular RNAs (circRNAs) were recognized to affect the development of colorectal cancer (CRC). Herein, we investigated the functions and mechanisms of circ_0067835 in CRC progression. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assay was performed to examine the expression of circ_0067835, microRNA-873-5p (miR-873-5p) and Mitogen-Activated Protein Kinase 1 (MAPK1). Cell counting kit (CCK)-8 assay and colony formation assay were used to assess cell proliferation, and flow cytometry was conducted to monitor cell apoptosis. Transwell assay was applied to detect cell migration and invasion. Western blot assay was implemented to determine the protein levels of MAPK1 and phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) pathway-related proteins. Interaction between miR-873-5p and circ_0067835 or MAPK1 was validated by dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Moreover, the role of circ_0067835 in vivo was evaluated via xenograft model assay. Circ_0067835 and MAPK1 were highly expressed in CRC tissues and cells, while miR-873-5p expression was downregulated. Depletion of circ_0067835 suppressed cell viability, clonogenicity, migration, invasion, survival, and the activity of PI3K/AKT pathway in CRC cells, while these effects were reversed by miR-873-5p inhibition. Circ_0067835 was mainly located at the cytoplasm, and it could sponge miR-873-5p. MiR-873-5p targeted MAPK1 to hamper cell proliferation and metastasis, and inactivated PI3K/AKT pathway. Additionally, circ_0067835 deficiency exerted an inhibitory effect on tumor growth in vivo. Circ_0067835 played an oncogenic role in CRC development through the miR-873-5p-MAPK1-PI3K/AKT pathway, offering a possible molecular strategy for CRC therapy.